Predictors of breast cancer screening uptake: a pre intervention community survey in Malaysia - Dahlui, M.; Gan, D.E.H.; Taib, N.A.; Pritam, R.; Lim, J. (2012)
Introduction: Despite health education efforts to educate women on breast cancer and breast cancer screening modalities, the incidence of breast cancer and presentation at an advanced stage are still a problem in Malaysia. Objectives: To determine factors associated with the uptake of breast cancer screening among women in the general population. Methods: This pre-intervention survey was conducted in a suburban district. All households were approached and women aged 20 to 60 years old were interviewed with pre-tested guided questionnaires. Variables collected included socio-demographic characteristics, knowledge on breast cancer and screening practice of breast cancer. Univariate and multivariate analysis were performed. Results: 41.5 of a total of 381 respondents scored above average; the mean knowledge score on causes and risks factors of breast cancer was 3.41 out of 5 (SD1.609). 58.5 had ever practiced BSE with half of them performing it at regular monthly intervals. Uptake of CBE by nurses and by doctors was 40.7 and 37.3, respectively. Mammogram uptake was 14.6. Significant predictors of BSE were good knowledge of breast cancer (OR=2.654, 95 CI: 1.033-6.816), being married (OR=2.213, 95 CI: 1.201-4.076) and attending CBE (OR=1.729, 95 CI: 1.122-2.665). Significant predictors for CBE included being married (OR=2.161, 95 CI: 1.174-3.979), good knowledge of breast cancer (OR=2.286, 95 CI: 1.012-5.161), and social support for breast cancer screening (OR=2.312, 95 CI: 1.245-4.293). Women who had CBE were more likely to undergo mammographic screening of the breast (OR=5.744, 95 CI: 2.112-15.623), p<0.005. Conclusion: CBE attendance is a strong factor in promoting BSE and mammography, educating women on the importance of breast cancer screening and on how to conduct BSE. The currently opportunistic conduct of CBE should be extended to active calling of women for CBE.